Social support, health literacy and anxiety among pregnant women during coronavirus 2019 pandemic in Thailand - Phutong, Piangkhuan; Thaithae, Suparp (Frontiers in Psychology, 2023)
The ongoing coronavirus disease 2019 (COVID-19) pandemic continues to have a significant impact. Pregnant women are particularly vulnerable to its effects, which may increase their anxiety levels. This study aims to investigate anxiety levels in pregnant women during the COVID-19 pandemic in Thailand and to identify factors predicting such anxiety.The researchers collected data through an online questionnaire from November 2021 to May 2022. The sample included 404 pregnant women. The questionnaire consisted of personal information, health literacy related to COVID-19, social support, and anxiety related to COVID-1 9 .The content validity of the questionnaire were verified by three experts, with content validity indices of . 8 7 , . 8 0 , and . 8 7 for each domain, respectively. The reliability of the questionnaire were . 9 6 for health literacy, .95 for social support, and .96 for anxiety. Moreover, in-depth telephone interviews were also conducted with pregnant women. The data were analyzed using descriptive statistics, stepwise multiple regression, and content analysis.Results: Group of 404 pregnant women were studied, and the results showed that pregnant women had a high level of health literacy regarding SD = 14.23) and social support level on a high level (mean = 83.99, SD = 11.34). Most of them were concerned about anxiety related to COVID-19 infection and pregnancy on a moderate level (mean = 47.78, SD = 11.49). The factors predicting the anxiety of pregnant women during the COVID-19 outbreak in Thailand included health literacy related to COVID-19 (β = .468) and social support (β = .283), with a prediction rate of 32.80% (R 2 =.328) with statistical significance (p < .05).This study revealed the anxiety level of pregnant women during the COVID-19 outbreak in Thailand, which was moderate. Health literacy about COVID-19 and social support can predict the anxiety level of pregnant women.